Effects of crosslinker chain-length on the fatigue life during recovery of shape memory polymers - Quek, Yue Heng (Nanyang Technological University, 2022)
In this current report, a study on the thermo-mechanical behaviour of shape memory polymers (SMPs) at various temperatures was conducted. By varying crosslinkers of difunctional monomers of different chain lengths (n = 2, 4 and 9), the effect of crosslinker length on the recovery stress, stress relaxation and yield time of SMPs were studied. Glass transition temperature (Tg) tests were first conducted to identify a suitable reference for Tg (peak of loss modulus). Stress recovery experiments were conducted to explore the effects of crosslinker length on recovery stress and yield time. It was observed that as crosslinker length increases, recovery stress increases while yield time decreases. Additionally, as recovery temperature with respect to Tg decreases, yield time exponentially increases. Given the exponential increase in yield time, the concept of time temperature superposition (TTS) was explored as a means to estimate the relaxation modulus of the sample at different temperatures. With a relaxation modulus master curve constructed, the yield time of the SMP could be approximated. Although challenges faced during this project are still aplenty, this work serves to pioneer and prove the viability of using the concept of TTS to predict the yield time of SMPs strained at different temperatures.